Freehand SPECT for sentinel lymph node detection in patients with head and neck cancer: first experiences. (January 2014) - Mandapathil, Magis; Teymoortash, Afshin; Heinis, Jochen; Wiegand, Susanne; Güldner, Christian; Hoch, Stephan; Roeßler, Marion; Werner, Jochen A
Abstract Conclusion: Feasibility of intraoperative 3D imaging with freehand (fh) SPECT for sentinel lymph node (SLN) biopsy in head and neck cancer (HNC) could be demonstrated. Controlled clinical studies are needed to evaluate its accuracy and impact on patient morbidity. Objectives: The clinical N0 neck in HNC needs improvement in management to sufficiently detect occult neck disease but to spare patients from potential morbidity by elective neck dissection. The SLN concept has potential to accurately stage the neck with low morbidity. Methods: fhSPECT is a 3D tomographic imaging modality with a gamma probe system combined with an infrared optical tracking system. Five patients with HNC and clinical N0 neck were recruited. Scanning for SLN using fhSPECT was performed before excision and selective neck dissection and specimens were analyzed histopathologically. Results: Preoperatively, a total of nine SLNs were located in five patients with fhSPECT. SLNs in three patients were positive for metastatic disease; in two patients the SLNs were tumor-free. No residual radioactivity was found in the neck in any of the patients after extirpation of SLNs. fhSPECT acquisitions took 2.6 ± 0.4 min. No metastatic lymph nodes were detected in any other node harvested during subsequent selective neck dissection in any patients.